0
0
mình cần gấp , cảm ơn nhé
Hãy luôn nhớ cảm ơn và vote 5*
nếu câu trả lời hữu ích nhé!
Đáp án:
`21.`
`A = ((6x + 1)/(x^2 - 6x) + (6x - 1)/(x^2 + 6x)) . (x^2 - 36)/(x^2 + 1)`
`A = [(6x + 1)/(x(x - 6)) + (6x - 1)/(x(x + 6))] . ((x - 6)(x + 6))/(x^2 + 1)`
`A = ((6x + 1)(x + 6) + (6x - 1)(x - 6))/(x(x - 6)(x + 6)) . ((x - 6)(x + 6))/(x^2 + 1)`
`A = (6x^2 + 36x + x + 6 + 6x^2 - 36x - x + 6)/(x(x^2 + 1))`
`A = (12x^2 + 12)/(x(x^2 + 1))`
`A = (12(x^2 + 1))/(x(x^2 + 1))`
`A = 12/x`
Vậy `A = 12/x`
`22.`
`B = (x^2 - 1)/(x + 10) . (2x)/(x + 2) + (x^2 - 1)/(x + 1) . (10 - x)/(x + 2)`
`B = (x^2 - 1)/(x + 10) . ((2x)/(x + 2) + (10 - x)/(x + 2))`
`B = (x^2 - 1)/(x + 10) . (2x + 10 - x)/(x + 2)`
`B = (x^2 - 1)/(x + 10) . (x + 10)/(x + 2)`
`B = (x^2 - 1)/(x + 2)`
Vậy `B = (x^2 - 1)/(x + 2)`
`23.`
`C = (x/(x - 1) - (x + 1)/x) : (x/(x + 1) - (x - 1)/x)`
`C = (x . x - (x - 1)(x + 1))/(x(x - 1)) : (x . x - (x - 1)(x + 1))/(x(x + 1))`
`C = (x^2 - x^2 + 1)/(x(x - 1)) : (x^2 - x^2 + 1)/(x(x + 1))`
`C = 1/(x(x - 1)) : 1/(x(x + 1))`
`C = 1/(x(x - 1)) . (x(x + 1))/1`
`C = (x + 1)/(x - 1)`
Vậy `C = (x + 1)/(x - 1)`
Hãy giúp mọi người biết câu trả lời này thế nào?
Bảng tin